ANALYSIS OF MSME DEVELOPMENT IN PEMATANGSIANTAR CITY - Reni Ria Armayani Hasibuan; Dwi Rahma; Nurhayati; Putra Apriadi Siregar; Fitri Hayati (IAIN Lhokseumawe, 2022)
UMKM has an important role’scause can be able to create business fields to support daily economic needs. Accounting knowledge and business experience is one of the factors in developing a business. This study aims to determine whether accounting knowledge and business experience affect the development of UMKM in Pematangsiantar City. This study uses primary data and secondary data. Primary data was obtained by distributing questionnaires to business actors in Pematangsiantar City, while secondary data was obtained through various literature studies and official websites. The respondents in this study amounted to 117 entrepreneurs. In this study, the researcher used a quantitative approach and processed the data obtained from the questionnaire which was transformed through a Likert scale. While the analysis used in this study is multiple linear regression with a significant level of 5%. From the results of the research conducted, it can be concluded that: 1) There is a positive influence between accounting knowledge and the development of UMKM in Pematangsiantar City, where the value of t.count is 3.994 > ttable of 1.65833. 2) There is a positive influence between business experience on the development of UMKM in Pematangsiantar city, where the tcount value is 2.631> ttable is 1.65833. 3) There is a positive influence between Accounting Knowledge and Business Experience on UMKM Development in Pematangsiantar City by 25.4%. This is evidenced by the value of the coefficient of determination R Square of 0.254.